Rejection, Humiliation, and Parole: A Study of Parolees' Perspectives. Issue 3 (30th June 2015) - Pogrebin, Mark R.; Stretesky, Paul B.; Walker, Alexandra; Opsal, Tara
<x xml:space="preserve">Abstract</x> Research on status rejection has developed considerably over the past two decades and is applied in a number of different settings to better understand criminal and deviant behavior. Our research contributes to that body of work by examining the ways in which status rejection may create a potentially humiliating dynamic for individuals on parole. Specifically, we use in‐depth interviews with parolees to illustrate how the parolee identity can promote the experience of status rejection and simultaneously foster conditions for humiliation—an emotional state that may impede one's ability to both (re) construct a conventional identity and reintegrate back into one's community.